2011
DOI: 10.1007/s10600-011-0004-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of 3,4-dihydropyrimidin-2-thione aminomethylene derivatives based on the alkaloid cytisine

Abstract: 547.94: 547.853 3,4-Dihydropyrimidin-2-thiones derivatized by the alkaloid cytisine were synthesized by Mannich aminomethylation. The compositions and structures of the products were confirmed by mass spectrometry and PMR and 1 H-1 H NOESY spectroscopy. One of the products showed pronounced antimicrobial activity.Keywords: alkaloid cytisine, PMR and 1 H-1 H NOESY spectroscopy, antimicrobial activity.Incorporation into the structure of plant alkaloids of other pharmacophores, including physiologically active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Thus, pyrimidine-2-thione Mannich base 145 ( Fig. 26) was obtained using natural alkaloid cytosine as amine reagent in aminomethylation, and its evaluation as antibacterial agent showed that it is a potent growth inhibitor of S. aureus and B. subtilis, and it has weak activity against P. aeruginosa and E. coli [209]. Double Mannich bases 146 ( Fig.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Thus, pyrimidine-2-thione Mannich base 145 ( Fig. 26) was obtained using natural alkaloid cytosine as amine reagent in aminomethylation, and its evaluation as antibacterial agent showed that it is a potent growth inhibitor of S. aureus and B. subtilis, and it has weak activity against P. aeruginosa and E. coli [209]. Double Mannich bases 146 ( Fig.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Kulakov synthesized new 3,4-dihydropyrimidin-2-thiones 28 in two steps: (i) a Biginelli reaction to obtain compounds 27 and (ii) an aminomethylation Mannich reaction to obtain 3,4-dihydropyrimidin-2-thiones grafted with alkaloid cytisine ( Scheme 9 ) [ 78 ]. The bioscreening of 28a revealed its pronounced antibacterial activity against the Gram-positive strains S. aureus and B. subtilis , weak activity against Gram-negative strains P. aeruginosa and E. coli , in addition to the fungus C. albicans .…”
Section: Biginelli Reaction Mediated Synthesis Of Antimicrobial Pyrimidine Derivativesmentioning
confidence: 99%
“…Among the various derivatives of cytisine, compounds are constantly found with other types of biological activity that are not characteristic of itself (antispasmodic, antiarrhythmic, hepatoprotective, analgesic, cholinergic, insecticidal, antioxidant, etc. ), which attracts attention and encourages the synthesis and study of its new derivatives [9,10]. Small doses of cytisine strongly arouse breathing and increase blood pressure.…”
Section: Introductionmentioning
confidence: 99%